FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBELIAN PUPUK BERSUBSIDI (STUDI KASUS PETANI PADI DI DESA O MANGUNHARJO) - Ira Primalasari; Syabawaihi (Program Studi Agribisnis Faperta Universitas Muhammadiyah Bengkulu, 2024)
The aim of this research is to analyze the factors that influence the purchase of subsidized fertilizer by rice farmers in Purwodadi District, Musi Rawas Regency. The types of data used in this research are primary data and secondary data. Primary data includes the characteristics of rice farmer households. Secondary data was obtained from various sources related to factors influencing the purchase of subsidized fertilizer. This research data collection technique uses observation techniques, interviews and library methods. The sample determination in this research was carried out using non-probability sampling techniques. Data analysis used in this research used quantitative descriptive analysis. Quantitative analysis uses multiple linear regression analysis. The research results show that of the seven research variables, the information factor has a significant influence on the purchase of subsidized fertilizer with a significance value of 0.000 ≤ α = 0.05. Meanwhile, the six factors, namely age, education, experience, land area, income and price, do not have a significant effect on purchasing subsidized fertilizer. Key words: farmer; purchase; subsidized fertilizer